The "what" and "how" questions of the healthy immigrant effect: Psychosocial resources and demands as pathways to mental health risks - Yang, Fei-Ju (My University, 2017)
Current research identifies gender, age, and ethnic patterns for the healthy immigrant effect related to mental health, but little research explores what determines immigrants’ mental health and how mental health deterioration occurs. This dissertation investigates the ‘what’ and the ‘how’ questions by applying the Social Determinants of Health (SDOH) Perspective and the Stress Process Model. To answer the ‘what’ question, this dissertation draws on the SDOH framework to examine potential social determinants—in the form of structural conditions, behavioral risks and psychosocial demands—affecting long-term immigrants’ lower mental health status. To approach the ‘how’ question, it employs the Stress Process Model to investigate the differential exposure to behavioral risks and psychosocial demands between recent and long-term immigrants. The analysis of the data from the Canadian Community Health Survey-Mental Health 2012 and the General Social Survey-Social Identity 2013 indicates that structural conditions, behavioral risks, and psychosocial demands co-influence immigrants' mental health to some extent. Behavioral risks have independent contributions to mental health, but the contributions are small. Psychosocial resources and demands, however, have the greatest impact on mental health. An examination of the relationships between length of migration and psychosocial resources indicates that, compared to recent immigrants, long-term immigrants are in the state of 'high support and high strain,’ and the differences in these psychosocial resources and demands translate into mental health differences (the so-called healthy immigrant effect) between long-term and recent immigrants.
Keywords: immigrants, mental health, social support, interpersonal stress, health behavior